Housing Question for Scholars: From a Communal House to a Cooperative - Dolgova, Evgeniya A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2021)
This article examines the transition from the principle of abolishing the way of life structured around the individual (communal house) to socially stratified comfortable housing (a cooperative) in the second half of the 1920s and mid-1930s. Traditionally, housing cooperatives are interpreted as an instrument of proletarian social stratification. The author studies industrial housing cooperatives of scholars, characterising the specifics of their interaction with the local authorities, clarifying their social composition, and reconstructing the peculiarities underlying the functioning and financial discipline. Using the documentation of the State Archives of the Russian Federation, the author explores the history of several Moscow, Leningrad, and regional scholarly cooperatives. Also, the author separately considers the project of the House for academic staff in Omsk illustrating the publication with an architectural drawing of a typical layout of elite accommodation. The author concludes that a short period of housing cooperation, which unfolded during the first five-year plan, could contribute to the strengthening of social stratification (scholars were taken out of the framework of general civil norms for housing), stratification within the academic community (financially successful categories of scholars were singled out), reducing the severity of the housing problem in the provinces (due to the resettlement of visiting specialists). On the other hand, the brief period cannot be considered successful due to the instability of cooperatives for researchers in the system of working housing, the small number of cooperatives and efforts to increase their administrative enlargement, the vagueness of the boundaries between municipal and cooperative housing, and, finally, the financial burden of cooperatives for scholars (with high state credit costs).